Enhancing rutting resistance of asphalt binder by adding plastic waste. Issue 1 (1st January 2018) - Abu Abdo, Ahmad M.; Khater, Mohammed E.
Abstract: Ras Al Khaimah, UAE is well known in the region for its industrial sectors. As a result, its road network is enduring heavy traffic loads. When accompanied by hot temperatures during the summer these roads fail prematurely due to permanent deformation (rutting). To avoid this problem, asphalt binder with high stiffness should be used, which is expensive and not eco-friendly. The objective of this study was to evaluate the addition of different percentages of plastic waste powder obtained by grinding waste bottle plastics on different asphalt binders' properties. Test results showed that adding plastic waste to asphalt binder increased its viscosity and G */sin δ values. Furthermore, it was observed that when adding waste plastic, the tested binder grades would meet Superpave Asphalt Binder Specifications for higher binder grades. Thus, adding plastic waste to asphalt binder could be considered as a cheaper and environmental friendly solution, when compared to the use of higher binder grades to reduce rutting in asphalt pavements in Ras Al Khaimah roads.